Surgical Outcomes of Vaginal or Cervical Melanoma - Tian, Hui; Wang, Xuan; Lian, Bin; Si, Lu; Gao, Min; Zheng, Hong; Chi, Zhihong; Kong, Yan; Mao, Lili; Bai, Xue; Tang, Bixia; Yan, Xieqiao; et al. (Frontiers in Surgery, 2022)
Objective To evaluate the effectiveness of radical resection compared with nonradical resection for vaginal or cervical melanoma. Methods We retrospectively analyzed the clinical data of postoperative patients with primary lower genital tract melanoma hospitalized in Peking University Cancer Hospital between Jan 2014 and Dec 2020. The study endpoints were recurrence-free survival (RFS) and overall survival (OS). Using Kaplan–Meier method-plotted survival curves, univariate and multivariate Cox proportional hazards regression models were used to identify the factors associated with RFS and OS and to calculate the hazard ratio (HR) and its associated 95% confidence interval (95% CI). Results A total of 80 patients were included. Thirty-one patients had received nonradical resection, and 49 patients had received radical resection. The median patient age was 55.5 (IQR 45.3–60.0) years. Sixty-two (77.5%) patients had vaginal melanoma. Sixty-four patients (80.0%) had received postoperative adjuvant therapy. The median follow-up time was 36.0 months (95% CI 10.1–62.1 months). Sixty-four patients developed recurrence, and 44 patients died. The median RFS (mRFS) was 6.0 months (95% CI 3.4–8.6 m), and the RFS for the radical resection group was longer than that for the nonradical resection group (9.5 vs. 5.3 m), without significant difference (P>0.05). The median OS (mOS) was 25.9 months (95% CI 14.4–37.4 m). The mOS was 24.6 months (95% CI 10.3–38.9 m) and 25.9 months (95% CI 10.9–40.9 m) in nonradical /radical resection group respectively. Univariable Cox regression analysis showed that the surgical approach, infiltration depth of the tumor, lymph node metastasis, and postoperative adjuvant therapy were independent risk factors for RFS and that postoperative adjuvant therapy was an independent risk factor for OS. Conclusion We observed that surgical procedures were associated with RFS by performing multivariate analysis, which corrected for potential confounding factors, and we did not appreciate the survival benefit from radical surgery in vaginal melanoma and cervical melanoma.